Tinjauan Hukum dan Implementasi Pemutakhiran Kartu Keluarga dalam Meuwujudkan Ketunggalan Identitas di Kabupaten Gresik - Nurul Puspita Wardani* (Airlangga Development Journal, 2018)
In 2008, the Ministry of Home Affairs recorded the Electronic Population Identity Card (e-KTP) with the main objective of establishing an orderly population administration through the issuance of 1 (one) Population Registration Number (NIK) for 1 (one) resident. The issuance of NIK-based national ID cards is supported by building accurate population databases at the Regency / City, Provincial and Central levels which are connected online using the Population Administration Information System (SIAK). High population mobility experienced by Gresik as one of the bases of the East Java  and  Surabaya  suburban  industries and  other metropolitan  cities is strongly influenced by the behavior of the people with the tendency of residents to approach work sites but there is no desire to settle in the area of work or population movements in time short between the workplace and his residence. the formulation of the problems discussed are as follows, first, what is the legal review of laws and regulations governing population administration and civil records to provide a normative basis for the implementation of family card updates; population. The approach used in this study is the socio-legal approach. The Innovation of My Family Card Re-Data (Kakek Ku Datang) The Civil Registry Population Office of Gresik Regency is a solution to establish an orderly population administration in Gresik.  The  Kakek  Ku  Datang  program  is  one  of  the  best  practices  in reviving local resources at the village level to support the implementation of services or regional development programs, as well as being an example of responsive services to the community supported by an interactive system that provides communication space for the public through application and socialization media.